Mitral valve repair. Quadrangular resection of the posterior leaflet in patients with myxomatous degeneration - Pomerantzeff,Pablo Maria Alberto (1999)
OBJECTIVE - To analyze the immediate and late results of mitral valve repair with quadrangular resection of the posterior leaflet without the use of a prosthetic ring annuloplasty. METHODS - Using this technique, 118 patients with mitral valve prolapse who underwent mitral repair from January '84 through December '96 were studied. Age ranged from 30 to 86 (mean = 59.1±11.8) years and 62.7% were males. An associated surgery was performed in 22% of the patients, and coronary artery bypass graft was the most frequently performed surgery (15 patients - 12.7%). In 20 (16.9%) patients other associated techniques of mitral valve repair were used and shortening of elongated chordae tendineae was the most frequent one (6 patients). RESULTS - Immediate mortality was 0.9% (one patient). Long-term rates for thromboembolism, endocarditis, re-operation and death in the late postoperative period were 0.4%, 0.4%, 1.7% and 2.2% patients/year, respectively. The actuarial curve of survival was 83.8±8.6% over 12 years; survival free from re-operation was 91.8±4.3%, free from endocarditis was 99.2±0.8% and free from thromboembolism was 99.2±0.8%. In the late postoperative period, 93.8% of the patients were in functional class 1 (NYHA), with a complete follow-up in 89.7% of the patients. CONCLUSION - Patients with mitral valve prolapse who undergo mitral valve repair using this technique have a satisfactory prognosis over 12 years.